Global migration and transmission of disease: A Malaysian case study - Mohd Zain, S.N.; Lim, Y.A.L.; Sahimin, N. (2017)
Mass migration from less developed to more developed countries have created a shift in the global population. Urbanization and extension in industrialization of developing nations have resulted in millions migrants migrating to major urban cities around the globe to cope with expanding workforce. This has attracted many to flock to major cities in Malaysia both legal and illegally from the South East Asia (Indonesia, Cambodia, Vietnam, the Philippines and Myanmar) and South Asian countries (Nepal, India and Bangladesh) where endemic infections are very much prevalent and most likely to pose public health problems to the local community. Presently, compulsory medical screening for workers prior entering to the workforce does not include parasitic screening. As the number of migrant workers has grown exponentially over the past decade and the incidents of communicable disease have become more prevalent in the country, therefore, there is an acute need for a more accurate and current information on the parasitic infections in this particular group of workers and factors associated to infections as it impacts the local community significantly.